Walking the Tightrope: Counterproductive Work Behavior as Compensation for Citizenship Demands - Spanouli, Andromachi; Hofmans, Joeri (Frontiers in Psychology, 2016)
Amidst a struggling economy, organizations are ruled by the survival of the fittest paradigm but it is the employees who tend to pay the price, with increased demands which, oftentimes, fall outside their job scope. In the present paper, we examined whether pressuring people to engage in such organizational citizenship behaviors (OCB) might in fact backfire and lead to increased Counterproductive Work Behavior (CWB) because of compensatory mechanisms. We propose a typology of OCB that distinguishes between discretionary and elicited OCB, hypothesizing that elicited but not discretionary OCB, positively relates to CWB. By doing so, we wanted to examine if such a distinction can explain conflicting past results concerning the within-person OCB–CWB link, and to test whether increased citizenship demands can have an adverse effect for the organization. Our hypothesis was tested by asking 29 employees twice a day for 10 consecutive working days to report on the elicited and discretionary OCB and CWB they performed (N = 210 responses). Multilevel logistic regression analyses showed that elicited OCB was positively related to CWB, whereas discretionary OCB was not related to CWB. This finding steers theorizing away from the conventional classification of employees as bad apples versus good soldiers, by revealing that CWB can positively relate to OCB as a result of compensatory mechanisms. From a practical point of view, our results imply that employers should be mindful of the unintended consequences that OCB might entail when employees perceive that they are expected to engage in such behaviors.